2020
DOI: 10.1016/j.isci.2020.100884
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Aerosol Modulates the Oral Microbiome and Increases Risk of Infection

Abstract: The trend of e-cigarette use among teens is ever increasing. Here we show the dysbiotic oral microbial ecology in e-cigarette users influencing the local host immune environment compared with non-smoker controls and cigarette smokers. Using 16S rRNA high-throughput sequencing, we evaluated 119 human participants, 40 in each of the three cohorts, and found significantly altered beta-diversity in e-cigarette users (p = 0.006) when compared with never smokers or tobacco cigarette smokers. The abundance of Porphyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
134
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 53 publications
(54 reference statements)
7
134
1
5
Order By: Relevance
“…By using invasive E. coli in co-culture studies with EDMs, we also determine that handling of microbes by the gut epithelium was fundamentally impaired upon chronic and repetitive exposure to e-cig, resulting in higher infectivity and inflammation. Our findings are in keeping with prior studies showing higher infectivity and inflammation in the epithelial lining of the oral mucosa (25) and the lung (36)(37)(38).…”
Section: E-cigarettes Trigger Gut Inflammationsupporting
confidence: 93%
See 1 more Smart Citation
“…By using invasive E. coli in co-culture studies with EDMs, we also determine that handling of microbes by the gut epithelium was fundamentally impaired upon chronic and repetitive exposure to e-cig, resulting in higher infectivity and inflammation. Our findings are in keeping with prior studies showing higher infectivity and inflammation in the epithelial lining of the oral mucosa (25) and the lung (36)(37)(38).…”
Section: E-cigarettes Trigger Gut Inflammationsupporting
confidence: 93%
“…The gut is resident to diverse microbiota (symbionts and pathobionts) and its handling of and response to the same is known to regulate several chronic diseases such as inflammatory bowel diseases (IBD), obesity, cardiovascular diseases, cancers and rheumatoid arthritis (24). Beyond the fact that e-cigarette use significantly modulates the oral microbiome by increasing the abundance of oral pathobionts (25), but is not known to significantly impact the gut microbiome (26), nothing is known as to how e-cigarette use may influence the gut barrier. Using a combination of mouse models, transcriptomics, and murine and human gut-derived organoids as ex vivo near-physiologic model systems, here we expose the hitherto unknown effects of e-cigarettes on the gastrointestinal tract and provide insights into the potential long-term effects of e-cigarettes on health.…”
Section: Introductionmentioning
confidence: 99%
“…The overall trend in e-cigarette smoking among adolescents (middle school [10-14 years] and high school [14-18 years]) students is higher than in the adult population. The number of current adolescent e-cigarette users has experienced an upward trend since e-cigarettes first arrived in the United States [1][2][3]. According to a US Health and Human Services report in 2017, a nonlinear increase for current use of e-cigarettes among high school students from 1.5 to 11.3% between 2011 and 2017 occurred.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, it found that over 1400 respiratory cases linked to VALI in the United States, a term characterised by respiratory distress with bilateral (sometimes haemorrhagic) infiltrates within 3 months of using ENDS/ ENNDS 83 . Aside from respiratory illness, recent studies also found that vaping can change the oral and lung microbiome, leading to implications in cavities, gum disease and other health issues 84 . The oral microbiome in participants who vape was found to contain significantly higher levels of Porphyromonas and Veillonella bacteria, the latter being found in cigarette smokers as well.…”
Section: Concentration (Ppm)mentioning
confidence: 99%
“…The oral microbiome in participants who vape was found to contain significantly higher levels of Porphyromonas and Veillonella bacteria, the latter being found in cigarette smokers as well. The altered microbiome was found to contribute to a higher concentration of inflammatory response cytokines 84 . It also remains to be seen whether a history of VALI could pose higher risks for influenza and other viral lung infection complications 85 .…”
Section: Concentration (Ppm)mentioning
confidence: 99%